Research on The International Legal Protection of China’s Overseas Interests in The Construction of “Belt and Road” Based on The Perspective of Bilateral Treaties - Xu, Nawei (Transactions on Economics, Business and Management Research, 2024)
Western powers have been interfering in the internal affairs of some countries along the Belt and Road, promoting "hegemonic diplomacy", and thus affecting the economic interests of Chinese citizens and enterprises in local investment, trade and other activities. In the process of promoting the construction of the Belt and Road, the biggest risk facing my country’s overseas interests is the change of foreign regimes and political turmoil. In order to prevent and resolve the risks that hinder cooperation, especially the problems of project suspension, contract cancellation, and investment loss caused by regime change, it is urgent to find solutions with international credibility and authority, and with a certain degree of compulsion. International rule of law is recognized as the most effective way to resolve cross-border disputes and disputes to form international consensus and legitimacy. After studying the legal mechanism for protecting overseas interests, this article proposes to promote the protection of my country’s overseas interests by creating new bilateral treaties specifically for the construction of the Belt and Road. In the construction of the Belt and Road, my country should actively use international rule of law to shape rules, and while effectively protecting my country’s overseas interests, express its advocacy of international governance and international order, which is in line with the reality of my country’s growing economic strength and rising international status.